Neuroanatomical association of hypothalamic HSD2-containing neurons with ERα, catecholamines, or oxytocin: implications for feeding? - Askew, Maegan L.; Muckelrath, Halie D.; Johnston, Jonathon R.; Curtis, Kathleen S. (Frontiers in Systems Neuroscience, 2015)
This study used immunohistochemical methods to investigate the possibility that hypothalamic neurons that contain 11-β-hydroxysteroid dehydrogenase type 2 (HSD2) are involved in the control of feeding by rats via neuroanatomical associations with the α subtype of estrogen receptor (ERα), catecholamines, and/or oxytocin. An aggregate of HSD2-containing neurons is located laterally in the hypothalamus, and the numbers of these neurons were greatly increased by estradiol treatment in ovariectomized rats compared to numbers in male rats and in ovariectomized rats that were not given estradiol. However, HSD2-containing neurons were anatomically segregated from ERα-containing neurons in the Ventromedial Hypothalamus and the Arcuate Nucleus. There was an absence of oxytocin-immunolabeled fibers in the area of HSD2-labeled neurons. Taken together, these findings provide no support for direct associations between hypothalamic HSD2 and ERα or oxytocin neurons in the control of feeding. In contrast, there was catecholamine-fiber labeling in the area of HSD2-labeled neurons, and these fibers occasionally were in close apposition to HSD2-labeled neurons. Therefore, we cannot rule out interactions between HSD2 and catecholamines in the control of feeding; however, given the relative sparseness of the appositions, any such interaction would appear to be modest. Thus, these studies do not conclusively identify a neuroanatomical substrate by which HSD2-containing neurons in the hypothalamus may alter feeding, and leave the functional role of hypothalamic HSD2-containing neurons subject to further investigation.